Perception of Final Year Undergraduate Students of Agriculture at the University Of Ghana on Self-Employment in Agribusiness - Shiraz, H. (University Of Ghana, 2017)
Agriculture has been the backbone of Ghana’s economy for several decades. A continuous decline in the agricultural sector contribution to GDP over the years with increasing unemployment among graduates has raised concerns among researchers. The sector is dominated by aging and illiterate population which has negative impact on productivity and technology adoption. The educated youth who can contribute positively to the development of the sector are not taking advantage of opportunities in the agricultural sector. This study assesses the perception of students on self-employment in agribusiness. The factors that influence agricultural students’ decision on self-employment in agribusiness and perceived constraints students could face in taking up agribusiness enterprises were examined. The study population was final year undergraduate students in the School of Agriculture at the University of Ghana. A total of 150 students were selected through simple random sampling technique from the cluster of Departments. Descriptive statistics, Probit regression model and Kendall’s Coefficient of concordance (W) were used to address various objectives of the study. Results from the study showed that about 86% of the sampled students expressed intention to venture into self-employed agribusiness. Perception index from the analysis was found to be 0.62, indicating that students have a positive perception for self-employment in agribusiness. Significant factors that influence students’ decision to take up self-employment in agribusiness were identified as age, sex, department of the respondent, parents’ occupation and perception index. Major factors identified and ranked as the main constraints in order of importance were; lack of skills and knowledge, climate change, lack of access to credit, access to land, poor technological knowhow, market unavailability, lack of government support, poor extension service. Majority of the students want to have both theoretical and practical training in taking courses in agriculture. It is recommended that government and the private sector should develop policies and programmes to help address these constraints. Students of Agriculture should be properly oriented regarding the prospects of agriculture and its related businesses as an avenue for self- employed job creation.
Thesis (MPhil.)
Keywords: Perception; Self-Employment; Agribusiness; Ghana